Temporary Agency Workers: Social Characteristics and Employment - КозинаИрина Марксовна (Journal of Economic Sociology, 2012)
The article is devoted to new forms of employment being formed under conditions of agency work (or leasing labour). The human capital theory postulates that marginal social groups are mainly involved into temporary agency work which doesn’t provide workers with social guarantees. It can be found on the lowest step of the social ladder. So, social costs of increase in labour market flexibility may be very high and show up discrimination of agency workers, pushing them away from the labour market core and transforming them into working poors. The author considers the issues related to agency work in terms of social guarantees and proposes critical views on different topics including social characteristics of groups involved into agency work, motivation for getting jobs, assessment of work conditions, work satisfaction, etc. Empirical data is generated from the survey of 1012 temporary agency workers employed for Kelly Services, Adecco and Ancor in seven Russian regions. Research findings show that the structure of shared views on work agency is fragmented. It is resulted from co-existence of different demands in labour markets including demand for flexible employment. Comparing to labour markets in different countries the Russian one has some peculiarities. One of them implies that high educated young people are dominant among agency workers. They consider leasing labour as a direct way to stable employment. From the long term perspective temporary workers are oriented to getting stable positions and standard employment. It is concluded that temporary work practices are not discriminative and comparable with the overall labour markets in Russia.